(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2022)
Introduction: Every year millions of people fall sick with Tuberculosis (TB). Multidrug-resistant tuberculosis (MDR-TB) has a life threatening public health crisis globally. Objective: To determine the successful treatment outcomes of MDR-TB in Bangladeshi population. Methods: This retrospective cohort study was conducted at the National Institute of Diseases of the Chest and Hospital (NIDCH) Mohakhali, Dhaka, on 224 patients enrolled within July 2014 to June 2015. Data were collected by face-to-face interview and reviewing medical records. Results: A total of 224 MDR-TB patients’ histories were studied, among them male and female were 71% and 29% respectively. The average age was 37.6± 13.7 years. Of the total MDR-TB patients, 49(21.9%) were successfully treated, 124 (55.4%) had completed, 3(1.3%) had treatment failure, 5(2.2%) were lost to follow-up, 1(0.4%) was XDR-TB and 29 (12.9%) died. This study also found out that the patient with advanced age (≥55;p<0.001), living in rural areas (p<0.01), history of missing dose(p<0.001) and co-morbidity after treatment (p<0.05) were significantly associated with poor treatment outcomes of MDR-TB. Conclusion: The study concluded that the successful treatment outcomes were 77.2% and the mortality rate was 12.9% of MDRTB patients. Living in rural areas and missing dose were significantly associated with poor treatment outcomes. So, the study demonstrated that it is necessary to ensure the completion of whole treatment course to manage TB patients effectively in order to prevent MDR-TB. JAFMC Bangladesh. Vol 18, No 1 (June) 2022: 57-60